Replacement of Copper Cyanide by Copper Sulfate on Electroless Brass Plating Process - Dominguez-Rios, Carlos (European Journal of Applied Sciences, 2020)
Environmentally friendly processes and health protection are industrial requirements nowadays. Surface finishing industry demands the improvement of the composition of bath solutions, and specifically, reduction or elimination of the use of toxic substances to simplify complexity on wastewater treatment. This work presents results on the replacement of copper cyanide by copper sulfate in the composition of an electroless brass plating bath used on zamak alloy coating. The effect of the concentration of copper sulfate on the morphological and brass film color characteristics was studied. Characterization of plated pieces was made by scanning electron microscopy, optical microscopy, L*, a*, b* color parameters and by spectrophotometry and electrochemical techniques. Results indicate that copper cyanide can be successfully substituted, being possible to control the color of brass plating on this new process.